J-resistance curve testing of a pressure vessel steel and a clad pipe girth weld using clamped SE(T) specimens and the normalization method. (December 2021) - Barbosa, Vitor S.; Ruggieri, Claudio
Abstract: This work addresses an exploratory application of the normalization method to determine crack growth resistance curves for a typical pressure vessel steel and a clad pipe girth weld using clamped SE(T) specimens. A primary objective is to verify the effectiveness of the methodology in providing accurate descriptions of the ductile properties for the tested materials using clamped SE(T) specimens. Fracture toughness testing conducted on an A285 Gr C pressure vessel steel and a dissimilar Nickel–Chromium girth weld provides the load–displacement data from which J -resistance curves are evaluated on the basis of the normalization procedure. For the tested pressure vessel steel and clad pipe girth weld, the normalization method provides experimental measurements of ductile crack extension in terms of J − Δ a curves which are in good agreement with experimentally measured crack growth responses derived from the UC procedure. Highlights: Application of the normalization method using low constraint, clamped SE(T) specimens. J - R curves derived from the unloading compliance procedure and normalization method. The normalization method is an effective alternative to the unloading compliance procedure. Strong effect of the final crack length on J - R curves derived from the normalization method. The crack extension defining the anchor point should not exceed 15 ∼ 20% of the remaining ligament.